A novel RAB39B mutation and concurrent de novo NF1 mutation in a boy with neurofibromatosis type 1, intellectual disability, and autism: a case report - Claudia Santoro (BMC Neurology, 2020)
Abstract Background Mutations in RAB39B at Xq28 causes a rare form of X-linked intellectual disability (ID) and Parkinson’s disease. Neurofibromatosis type 1 (NF1) is caused by heterozygous mutations in NF1 occurring de novo in about 50% of cases, usually due to paternal gonadal mutations. This case report describes clinical and genetic findings in a boy with the occurrence of two distinct causative mutations in NF1 and RAB39B explaining the observed phenotype. Case presentation Here we report a 7-year-old boy with multiple café-au-lait macules (CALMs) and freckling, severe macrocephaly, peculiar facial gestalt, severe ID with absent speech, epilepsy, autistic traits, self-harming, and aggressiveness. Proband is an only child born to a father aged 47. Parents did not present signs of NF1, while a maternal uncle showed severe ID, epilepsy, and tremors.By RNA analysis of NF1, we identified a de novo splicing variant (NM_000267.3:c.6579+2T>C) in proband, which explained NF1 clinical features but not the severe ID, behavioral problems, and aggressiveness. Family history suggested an X-linked condition and massively parallel sequencing of X-exome identified a novel RAB39B mutation (NM_171998.2:c.436_447del) in proband, his mother, and affected maternal uncle, subsequently validated by Sanger sequencing in these and other family members. Conclusions The case presented here highlights how concurrent genetic defects should be considered in NF1 patients when NF1 mutations cannot reasonably explain all the observed clinical features.